Lmo2 Induces Hematopoietic Stem Cell‐Like Features in T‐Cell Progenitor Cells Prior to Leukemia123. (24th April 2013) - Cleveland, Susan M.; Smith, Stephen; Tripathi, Rati; Mathias, Elizabeth M.; Goodings, Charnise; Elliott, Natalina; Peng, Dunfa; El‐Rifai, Wael; Yi, Dajun; Chen, Xi; Li, Liqi; Mullighan, Charles; et al.
Abstract LIM domain only 2 (Lmo2) is frequently deregulated in sporadic and gene therapy‐induced acute T‐cell lymphoblastic leukemia (T‐ALL) where its overexpression is an important initiating mutational event. In transgenic and retroviral mouse models, Lmo2 expression can be enforced in multiple hematopoietic lineages but leukemia only arises from T cells. These data suggest that Lmo2 confers clonal growth advantage in T‐cell progenitors. We analyzed proliferation, differentiation, and cell death in CD2‐Lmo2 transgenic thymic progenitor cells to understand the cellular effects of enforced Lmo2 expression. Most impressively, Lmo2 transgenic T‐cell progenitor cells were blocked in differentiation, quiescent, and immortalized in vitro on OP9‐DL1 stromal cells. These cellular effects were concordant with a transcriptional signature in Lmo2 transgenic T‐cell progenitor cells that is also present in hematopoietic stem cells (HSCs) and early T‐cell precursor ALL. These results are significant in light of the crucial role of Lmo2 in the maintenance of the HSC. The cellular effects and transcriptional effects have implications for LMO2‐dependent leukemogenesis and the treatment of LMO2‐induced T‐ALL. STEM CELLS 2013;31:882–894